La plus entière bonne foi - Moreau, Rémi (Assurances, 1993)
Traditionally, contractual obligations between the insurer and the insured have been based on the Utmost Good Faith notion, in English and French laws, in Canadian Common Law and in Quebec Civil Code. ln examining this doctrine, the author tries to define what it is, where it applies and how court decisions interpret it.